Kurdish political assassination in the Kurdish Emirates During the centuries (4th and 5th A. H / 10th and 11th A.D) - Abush, Farhad H. (Humanities Journal of University of Zakho, 2017)
This study aims to highlight the phenomenon of political assassination in the Kurdish Emirates during the centuries (4th and 5th A. H / 10th and 11th A.D). This phenomenon is one of the most dangerous developments that occurred in these Emirates. The fourth and fifth A.H centuries/ tenth and eleventh A.D centuries considers among the most important centuries in the Islamic history for the Kurds. The Kurds demonstrated political and civilization development as they established Emirates in their country. These Emirates become among the strong political power that had to take into consideration and they become among the strongest Islamic power in the region. Therefore, the political assassination was not a strange phenomenon in the Kurdish Emirates. But, it has been repeated in most of the Kurdish Emirates; and affected princes, ministers and leaders, governors and others. The study was divided beside the introduction and conclusion to two sections, the first section devoted to talk briefly about political assassination in Islam. While, the second section focused on the political assassination in the Kurdish Emirates during the centuries (4th and 5th A. H / 10th and 11th A.D); and this was divided into two parts. The first part is devoted to the causes and motivations of the political assassinations in the Kurdish Emirates, as a conflict and competition over power among the ruling family, treason, conspiracy, and revenge. While the second part dedicated to the study of the methods and means of assassinations in the Kurdish Emirates. And among the most practiced method was assassination by poisons, stab to death by swords and knives, chopping heads and others.